(untitled) (Bangladesh Journal of Medicine, 2015)
Introduction: Use of blood means providing the right blood product, in the right quantity, for the right patient. It can help in bridging the gap between demand and supply of the precious blood or blood products. Objective: The present study was designed to study appropriateness of use of the blood components in different wards in DMCH, to improve the consistency and appropriateness of transfusion practice, to promote the integration of quality management systems into transfusion practice, to reduce the overall number of transfusion-related complications, to increase consumer awareness of the benefits and risks of blood component therapy; and conserve a limited resource. Methodology: This study was done at Transfusion Medicine Department of Dhaka Medical College Hospital in the period between January 2008 to December 2011. Donors of 18 to 55 years of both sexes were selected after reviewing the questionnaire, physical and medical examination and written consent .Blood was collected in different blood bags. Blood components were prepared by centrifugation of whole blood in a refrigerated centrifuge machine. Data was collected using a pretested questionnaire on age, gender, department, haemoglobin levels, indications of blood transfusions, types of product advised, total number of units ordered, cross-matched and transfused. Rational use of blood was assessed by determining prevalence of appropriateness using World Health Organisations clinical practical guidelines and transfusion indices. Interviews were done with doctors to assess their knowledge and practices. Result: In 2008, 1231(8.4%) components were prepared against 14560 whole blood. In 2009, 1636 (9.63%) components against 16984 whole blood were prepared. In 2010, 1380 (8.13%) components were prepared against 16980 whole blood. In 2011 1800 (8.91%) components were prepared and supplied to surgery, medicine, gynae, paediatrics, haematology and oncology wards. Conclusion: The hospital was not rationale in use of blood. Bangladesh J Medicine Jan 2015; 26 (1) : 18-24